MARUSYA CHURAI IN UKRAINIAN SPIRITUALITY - Макаровський, І. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article investigates the life and work of Marusya Churai, its prominent place and role in the Ukrainian spiritual culture.